Dissipation and mixing during the onset of stratification in a temperate lake, Windermere. (31st December 2014) - Simpson, John H.; Lucas, Natasha S.; Powell, Ben; Maberly, Stephen C.
Abstract Acoustic Doppler Current Profilers and chains of temperature sensors were used to observe the spring transition to stable stratification over a 55‐d period in a temperate lake. Observations of the flow structure were complemented by measurements of dissipation, based on the structure function method, near the lake bed and in the upper part of the water column. During complete vertical mixing, wind‐driven motions had horizontally isotropic velocities with roughly equal barotropic and baroclinic kinetic energy. Dissipation was closely correlated with the wind‐speed cubed, indicating law of the wall scaling, and had peak values of ∼ 1 × 10−5.5 W kg−1 at ten meters depth during maximum wind forcing (W ∼ 15 m s−1). As stratification developed, the flow evolved into a predominantly baroclinic regime dominated by the first mode internal seiche, with root mean square axial flow speeds of ∼ 2–3 cm−1; ∼ 2.5–times the transverse component. At 2.8 m above the bed, most of the dissipation occurred in a number of strong maxima coinciding with peaks of near‐bed flow. In the pycnocline, dissipation was low most of the time, but with pronounced maxima (reaching ∼ 1 × 10−5 W kg−1) closely related to the local velocity shear. The downward diffusive heat flux across the pycnocline over 27.5 d accounted for ∼ 70% of the temperature rise in the water column below. Total lake kinetic energy increased by a factor of three between mixed and stratified regimes, in spite of reduced wind forcing, indicating less efficient damping in stable conditions.